2016
DOI: 10.1118/1.4953835
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical framework for virtual IMRT QA using machine learning

Abstract: The Virtual QA process predicts IMRT passing rates with a high likelihood, allows the detection of failures due to setup errors, and it is sensitive enough to detect small differences between matched Linacs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 159 publications
(207 citation statements)
references
References 37 publications
8
196
1
2
Order By: Relevance
“…Figure 4 shows that after approximately 80 data patients, no further improvement is obtained on average in the testing error. This number is roughly half the number obtained by Valdes et al20 confirming that if the data are more homogeneous, that is, for Institution 2, only data from one Linac were analyzed, a smaller number of data points are needed to obtain a stable model.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…Figure 4 shows that after approximately 80 data patients, no further improvement is obtained on average in the testing error. This number is roughly half the number obtained by Valdes et al20 confirming that if the data are more homogeneous, that is, for Institution 2, only data from one Linac were analyzed, a smaller number of data points are needed to obtain a stable model.…”
Section: Resultssupporting
confidence: 53%
“…With our validation results, Virtual IMRT QA can predict gamma passing rates accurately within 3.5% as maximum empirical error observed. In addition, our previous work showed that 200 patient‐specific QA plans and results are required to train the virtual QA model to achieve an accurate prediction 20. The required training QA data should be readily available assuming a measurement‐based clinical patient‐specific QA program is in place, and should not impose additional measurement burden on the practicing physicist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations